ANALYSIS OF CONCENTRATED SOLAR POWER TECHNOLOGIES' FEASIBILITY, SELECTION AND PROMOTIONAL STRATEGY FOR BANGLADESH (Journal of Mechanical Engineering, 2015)
Bangladesh gets solar radiation of average 4-6.2KWh/m2/per day that shows a great opportunity for alltypes of solar power generation technologies ranging from small to large scale. However, solar power technologyis confined in only Photovoltaic (PV) technology though it deserves ideal condition for concentrated solar power(CSP) technologies of power generation. Accounting the limited source and depletion of fossil fuel as well asforeign currency that expense for imported oil, adaptation of CSP technology can brings a solution of futuresustainable and cheap source of power. This research has analyzed existing developed CSP technologies andtheir comparative characteristic. A study has been conducted to find out feasibility of CSP technologyimplementation and selection of suitable CSP plant for Bangladesh. The findings of this study can be helpful toformulate policies support tools to take into account the future solar energy and sustainable utilization, promotionand development for CSP technologies.